Novel candidate genes for lignin structure identified through genome-wide association study of naturally varying Populus trichocarpa - Bryant, Nathan; Zhang, Jin; Feng, Kai; Shu, Mengjun; Ployet, Raphael; Chen, Jin-Gui; Muchero, Wellington; Yoo, Chang Geun; Tschaplinski, Timothy J.; Pu, Yunqiao; Ragauskas, Arthur J. (Frontiers in Plant Science, 2023)
Understanding compositional variability of biomass, and especially lignin, is crucial to the development and implementation of financially viable, integrated biorefineries. In this study, a population of 409 three-year-old, naturally varying Populus trichocarpa genotypes were characterized by heteronuclear single quantum coherence (HSQC) nuclear magnetic resonance (NMR) to elucidate twelve structural properties of lignin. This phenotypic analysis revealed p-hydroxybenzoate units were not normally distributed and exhibited an overall negative trend with the syringyl:guaiacyl ratio. A subsequent genome-wide association study (GWAS) was conducted using approximately 8.3 million single nucleotide polymorphisms (SNPs) and a 0.05 minor allele frequency. The GWAS identified 756 genes that were significantly associated (-log10(p-value)>6) with at least one lignin phenotype. A network analysis was utilized to integrate additional lines of evidence for the involvement of identified genes in lignin biosynthesis. Several promising candidate genes were identified, many of which have not previously been reported to be associated with lignin or cell wall biosynthesis. These results provide a resource for gaining insights into the molecular mechanisms of lignin biosynthesis and new targets for future genetic improvement in poplar.